2013
DOI: 10.1007/s00424-013-1385-y
|View full text |Cite
|
Sign up to set email alerts
|

A mutation in the extracellular domain of the α7 nAChR reduces calcium permeability

Abstract: The α7 neuronal nicotinic acetylcholine receptor (nAChR) displays the highest calcium permeability among the different subtypes of nAChRs expressed in the mammalian brain and can impact cellular events including neurotransmitter release, second messenger cascades, cell survival, and apoptosis. The selectivity for cations in nAChRs is thought to be achieved in part by anionic residues which are located on either side of the channel mouth and increase relative cationic concentration. Mutagenesis studies have imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…In these experiments, an empty pcDNA3.1 vector was used as a transfection control. Consistent with findings on D44A function in hippocampal neurons (16), our calcium imaging data suggest that expression of this mutant significantly diminishes calcium flow through the α7. A confirmation of D44A expression in PC12 cells indicates that expression of D44A increases total fBgtx fluorescence (by 89±15%) without altering the overall cellular distribution of the signal (Supplemental Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In these experiments, an empty pcDNA3.1 vector was used as a transfection control. Consistent with findings on D44A function in hippocampal neurons (16), our calcium imaging data suggest that expression of this mutant significantly diminishes calcium flow through the α7. A confirmation of D44A expression in PC12 cells indicates that expression of D44A increases total fBgtx fluorescence (by 89±15%) without altering the overall cellular distribution of the signal (Supplemental Fig.…”
Section: Resultssupporting
confidence: 90%
“…A new mutant of the α7 (D44A; ref. 16) was used to examine the role of calcium flow in growth. PC12 cells transfected with D44A presented a lowered calcium response (–67±11%) compared to controls following choline treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has shown that a site‐specific mutation in the α7 subunit (α7 D44A ) decreases channel permeability to calcium (Colón‐Sáez and Yakel ). We have shown that α7 D44A successfully expresses in PC12 cells and mediates a weakened calcium transient response following choline stimulation (Nordman and Kabbani ).…”
Section: Resultsmentioning
confidence: 99%
“…; Liu et al . ; Nordman and Kabbani ), or α7 D44A (Colón‐Sáez and Yakel ) using Lipofectamine 2000 (Thermo Fisher). Construct DNA was purified using a maxi prep kit (Xymo Research, Irvine, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, cholinergic system inhibits pro-inflammatory cytokines release through α7-nAChRmediated toll like receptor (TLR) expression on the neurons (Kim et al, 2014;Pavlov et al, 2007).Activation of the α7-nAChRs on astrocytes in the hippocampus increases cytoplasmic calcium levels and participates in various mechanisms of neuroprotection perhaps via the calcium-dependent phosphatase calcineurin (Colón-Sáez and Yakel, 2013). Furthermore, α7-nAChR activation exerts anti-apoptotic effects on neuronal cells which reduce cleaved caspase 3 and inflammation induced by Aβ (Boatright and Salvesen, 2003;Colón-Sáez and Yakel, 2013;Luan et al, 2013;Ramin et al, 2011). It has been found that, α7-nAChR can effectively scavenge superoxide, hydroxyl and other free radicalsthrough Ca 2+ -dependent mechanisms (Liu and Zhao, 2004) which protects against oxidant stress-induced damage resulting from Aβ toxicity (Li et al, 2014).…”
Section: Resistant To Inhibitors Of Cholinesterase Proteinmentioning
confidence: 95%